2017
DOI: 10.2166/wst.2017.175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutrients removal (NO3-N, NH3-N and PO4-P) with Chlorella vulgaris, Pseudomonas putida, Bacillus cereus and a consortium of these microorganisms in the treatment of wastewater effluents

Abstract: In this research removal of NH-N, NO-N and PO-P nutrients from municipal wastewater was studied, using Chlorella vulgaris, Pseudomonas putida, Bacillus cereus and an artificial consortium of them. The objective is to analyze the performance of these microorganisms and their consortium, which has not been previously studied for nutrient removal in municipal wastewater. A model wastewater was prepared simulating the physicochemical characteristics found at the wastewater plant in Chapala, Mexico. Experiments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…and 57.1% in algae mix (Figure 1b). This result contrasted with PO4-P removal with Chlorella vulgaris of previous studies, which reduced only 4.30% of PO4-P [11]. The results of other studies mentioned the efficiency value of Chlorella sp.…”
Section: Po4-p Removalcontrasting
confidence: 86%
See 1 more Smart Citation
“…and 57.1% in algae mix (Figure 1b). This result contrasted with PO4-P removal with Chlorella vulgaris of previous studies, which reduced only 4.30% of PO4-P [11]. The results of other studies mentioned the efficiency value of Chlorella sp.…”
Section: Po4-p Removalcontrasting
confidence: 86%
“…reaching 98.7-99.8% with piggery wastewaters media [10] and 80.62% with domestic wastewater media [9]. The same results were produced in swine wastewater treatment with Chlorella vulgaris producing 40-90% NH3-N removal [11]. This study less of NH3-N removal because the COD/NH3N ratio very high with 678 mg/L/7,81 mg/L.…”
Section: Nh3+h2o→nh4oh→nh4+oh -supporting
confidence: 76%
“…There are a few experimental reports that have been working on different consortia of microalga species and bacteria for urban and industrial wastewater treatments [2,10]. The C. vulgaris and P. putida consortium inherently has shown to be a good nutrient and organic contaminants removal option in synthetic municipal wastewater compared to axenic cultures [11,12]. Lananan, et al 2014, reported a removal efficiency up to 99.15% of the total phosphorus concentration in domestic wastewater treatment by using Chlorella with an effective microorganism (EM-1) co-culture [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are some experimental studies which have been working with different species of microalgae and bacteria for urban and industrial wastewater treatments [3,11]. The consortium of C. vulgaris and P. putida, has demonstrated a good simultaneous nutrients removal (ammonium and phosphate) and organic contaminants in synthetic municipal wastewater, compared with the axenic cultures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, calculating and analyzing ExPas from the metabolic network of the consortium between C. vulgaris and P. aeruginosa, it is possible to estimate their phenotypic potential under different schemes. Our research group has been working in the evaluation of nutrients of removal by using different microorganisms and the consortium between them [13]. Consequently, this project provides a fundamental approach to enhance our understanding of biological system where microalgae and bacteria coexist as it occurs in most wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%